UNUSED POSSIBILITIES OF DETECTIVE ACTIVITIES - Zaleckis, Romualdas (Administrative and Criminal Justice, 2017)
Legal regulation of Lithuanian, Latvian, Russian private detectives activities provide additional opportunities for private detectives to create added value in their practice. Special laws of the countries in question that regulate their activities, give private detectives exclusive rights to provide detective services, therefore activities of other entities in this field is considered unlawful, and carries administrative and criminal liability. Another important statutory regulatory aspect of detective activities is that detectives can be recognized by law, within certain boundaries, to legally collect information about another persons private life, which is completely forbidden for any other private individual and collecting another person's private information, caries criminal and civil liability. And so the legislator has strictly limited the amount of entities that can provide services within the scope of detective activities and the content they are allowed to handle. The author presents two types of services as an example: the search of a debtor and his assets, a person's solvency and reliability evaluation. It is recommendable to employ educational measures to expand market demand for legal services that only detectives have the right to provide.